2017
DOI: 10.1016/j.jvs.2016.10.124
|View full text |Cite
|
Sign up to set email alerts
|

Implications of concomitant hypogastric artery embolization with endovascular repair of infrarenal abdominal aortic aneurysms

Abstract: Concomitant HAE with EVAR is associated with longer and more complicated hospital stays. Ischemic colitis is a rare complication of EVAR. HAE increases the risk of ischemic colitis and renal failure requiring dialysis. This study highlights the importance of hypogastric artery preservation during EVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…Even though previous studies reported a higher risk of ischemic colitis associated with hypogastric embolization, as high as 2.6% compared with 1.1% in the standard EVAR, 29 we did not observe similar findings in our study. The rate of ischemic colitis is approximately 1% in all patients regardless of the treatment modality.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Even though previous studies reported a higher risk of ischemic colitis associated with hypogastric embolization, as high as 2.6% compared with 1.1% in the standard EVAR, 29 we did not observe similar findings in our study. The rate of ischemic colitis is approximately 1% in all patients regardless of the treatment modality.…”
Section: Discussioncontrasting
confidence: 99%
“…The rate of ischemic colitis is approximately 1% in all patients regardless of the treatment modality. Although both our study and the study conducted by Farivar et al 29 used the ACS NSQIP database, our lower rate of ischemic colitis in hypogastric embolization could be explained by the inclusion of a new set of data from 2015 to 2017, which dramatically increased our sample size, and the fact that we excluded patients who underwent both IBD and HAE. Those patients probably had bilateral iliac aneurysms, and addressing both sides at the same time could dramatically affect pelvic perfusion more than unilateral intervention.…”
Section: Discussionmentioning
confidence: 81%
“…Concomitant hypogastric artery embolization with EVAR is associated with longer and more complicated hospital stays, increasing the risk of ischemic colitis and renal failure requiring dialysis. 24,25…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, there is considerable risk of ischemic complications. [3][4][5] Whereas most patients can tolerate unilateral IIA occlusion, identification of patients at high risk to develop adverse complications after IIA interruption has not yet been elucidated. Thus, both the European Society of Vascular Surgery and the Society of Vascular Surgery (SVS) in their updated guidelines 6,7 recommend the preservation of blood flow to at least one IIA.…”
Section: Introductionmentioning
confidence: 99%